Kajian Literatur: Pengendalian Hama Burung pada Berbagai Jenis Tanaman Pangan di Indonesia - Amrul Jihadi; Anjar Pranggawan Azhari (Jurnal Ilmiah Populer Inovasi-Sainsphere, 2026)
Avian pests pose a significant challenge to food production in Indonesia, causing substantial economic losses for farmers. This literature review summarizes the information available in the scientific literature from 2000 to 2025 on the diversity of avian pests, the extent of the damage they cause, the control methods employed, and their potential integration into an integrated pest management (IPM) system. Using leading academic databases such as ScienceDirect, ProQuest, and Google Scholar, this report identifies dominant species, such as the house sparrow (Lonchura punctulata) and other white-rumped shamas, that infest rice, causing yield reductions of up to 30–50%. The analysis shows that infestation severity depends not only on the pest population but also on the characteristics of the host plant, as exemplified by the susceptibility of the Rojolele rice variety. Various control techniques, from traditional physical and mechanical methods to sensor-based automated technologies, each have their advantages and disadvantages. Therefore, this report concludes that an integrated and holistic IPM approach is the most effective solution. This approach does not aim for complete eradication, but rather for controlling pest populations below the economic damage threshold, leveraging the dual role of birds as natural predators of insect pests.